Role of cognitive impairment in predicting the long-term risk of all-cause mortality: a 20-year prospective cohort study in China - Shuang Zhao; Han Yang; Haijuan Zhao; Miao Miao; Qingqing Wang; Yaru Wang; Yuying Yin; Xin Wang (Archives of Public Health)
Abstract Background There is limited evidence of the relationship between cognitive changes and all-cause mortality. And it has no report of population-attributable fraction (PAF) of mortality due to cognitive impairment in Chinese elderly. In light of this, we comprehensively examined the relationship between cognitive impairment and all-cause mortality after 20-year follow-up among the elderly Chinese. Methods This is an epidemiological survey with a 20-year prospective cohort study design. A total of 9093 participants came from the Chinese Longitudinal Healthy Longevity Survey 1998–2018 waves. Cox proportional hazards regressions were performed to analyze the relationship between baseline cognitive impairment status, the rate of change in the MMSE scores over two years and subsequent all-cause mortality. Results We observed a dose–response relationship between cognition and mortality. Compared to those with no impairment, elderly with mild (AHR = 1.11, 95% CI 1.05–1.18), moderate (AHR = 1.22, 95% CI 1.13–1.33) and severe (AHR = 1.30, 95% CI 1.19–1.42) cognitive impairment showed increased mortality risk. Elderly with rapid cognitive decline had 24% higher mortality risk than those with stable cognitive (AHR = 1.24, 95%CI 1.10–1.39). The PAF of mortality due to severe cognitive impairment was 3.69% (95%CI:2.36–5.25%). Impairment in the subdomain of naming foods (AHR = 1.12, 95% CI 1.04–1.21), registration (AHR = 1.18, 95% CI 1.11–1.26), attention and calculation (AHR = 1.13, 95% CI 1.07–1.21), copy figure (AHR = 1.13, 95% CI 1.06–1.20), delayed recall (AHR = 1.14, 95% CI 1.07–1.20) and language (AHR = 1.14, 95% CI 1.05–1.24) were independently associated with increased mortality risk among participants. Conclusion Baseline cognitive impairment was inversely associated with longevity among the elderly Chinese. The rapid cognitive decline increased all-cause mortality, and this risk would continue for 20 years. These findings underscore the crucial role of early detection and management of cognitive impairment in the elderly.